2017
DOI: 10.1080/02656736.2017.1309576
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperthermia on the immunomodulatory properties of human umbilical cord vein mesenchymal stem cells (MSCs)

Abstract: Hyperthermia increases cell proliferation of the peripheral blood mononuclear cells and modifies the cytokine profile in the presence of UCV-MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…We found >95% of cells to be viable, although data were not saved in images. In addition, literature reports have confirmed our observation that MSCs, including AMMSCs, do not undergo serious structural damage or molecular changes during or post-hyperthermia [11,13,36]. Another study has demonstrated that after receiving heat shock pretreatment at 42°C for 1 h, bone marrow MSCs display their lowest apoptotic rate, owing to the elevated expression of heat shock proteins (HSPs) HSP70 and HSP90 inside the cells [37].…”
Section: Growth Characterization Of Tumor Spheroids: Co-culture Accelerated Tumor Growthsupporting
confidence: 69%
“…We found >95% of cells to be viable, although data were not saved in images. In addition, literature reports have confirmed our observation that MSCs, including AMMSCs, do not undergo serious structural damage or molecular changes during or post-hyperthermia [11,13,36]. Another study has demonstrated that after receiving heat shock pretreatment at 42°C for 1 h, bone marrow MSCs display their lowest apoptotic rate, owing to the elevated expression of heat shock proteins (HSPs) HSP70 and HSP90 inside the cells [37].…”
Section: Growth Characterization Of Tumor Spheroids: Co-culture Accelerated Tumor Growthsupporting
confidence: 69%
“…Enlarged temperature enhanced the proliferation of UCV-MSC cocultured with mononuclear cells of the peripheral blood as well as expression of IL-10, TGF- β 1, and FOXP3 mRNAs. It had no effect on IL-17A and IFN- γ secretion and reduced CXCL12 [24]. In our experiments, sublethal temperature has induced preliminary senescence [25] which is a mechanism of maintenance of MSC genetic stability by excluding damaged cells from the proliferation pool.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, tumor-associated MSCs were observed to protect ovarian cancer from hyperthermia via the CXCL12/ CXCR4-axis [19]. Furthermore, heat-exposed MSCs exhibited reduced inhibitory effects on lymphocytes compared to untreated MSCs [20]. Besides the stem cells' potential role in tumor protection after hyperthermia, MSCs have shown to play a role in the regeneration of hyperthermia-treated normal tissues.…”
Section: Introductionmentioning
confidence: 99%